2020
DOI: 10.3389/fphys.2020.00876
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Olfactory Genes in the Antennal Transcriptome of the Stink Bug Halyomorpha halys

Abstract: The brown marmorated stink bug, Halyomorpha halys (Hemiptera: Pentatomidae), is a serious agricultural and urban pest that has become an invasive species in many parts of the world. Olfaction plays an indispensable role in regulating insect behaviors, such as host plant location, partners searching, and avoidance of predators. In this study, we sequenced and analyzed the antennal transcriptomes of both male and female adults of H. halys to better understand the olfactory mechanisms in this species. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 83 publications
(117 reference statements)
2
14
0
Order By: Relevance
“…We referred to a bioinformatics pipeline [32,33] to identify and annotate the members of the ORs in Hemiptera. We used the protein sequences of the known gene family in insects, downloaded from the National Center for Biotechnology Information (NCBI) as a database [12,23,25,[34][35][36][37][38][39][40], and the database was used to construct a hidden Markov Model (HMM) profile for the family. The genome sequence, proteome sequence, and general feature format (GFF) annotation file of each identified hemipteran species were used as input files.…”
Section: Identification and Annotation Of Odorant Receptor Familymentioning
confidence: 99%
“…We referred to a bioinformatics pipeline [32,33] to identify and annotate the members of the ORs in Hemiptera. We used the protein sequences of the known gene family in insects, downloaded from the National Center for Biotechnology Information (NCBI) as a database [12,23,25,[34][35][36][37][38][39][40], and the database was used to construct a hidden Markov Model (HMM) profile for the family. The genome sequence, proteome sequence, and general feature format (GFF) annotation file of each identified hemipteran species were used as input files.…”
Section: Identification and Annotation Of Odorant Receptor Familymentioning
confidence: 99%
“…It also functions as a repellent allomone to T. japonicus that significantly extends the host searching time of the parasitoid in the laboratory bioassays (Zhong et al, 2017). This alarm pheromone component was sensed by olfactory reception through H. halys OBP25, OBP30, OBP16, OBP8, and OBP4 in BMSB (Zhong et al, 2018;Sun et al, 2020). Interestingly, our results showed that TjapOBP3 was distantly related to H. halys OBP8.…”
Section: Discussionmentioning
confidence: 65%
“…This study show that T. papillosa and H. halys had the highest copies of unigenes. H. halys is a polyphagous pest native to East Asia ( Sparks et al, 2020 ; Sun D. D. et al, 2020 ). Unlike T. papillosa , H. halys exhibits a wide host range.…”
Section: Discussionmentioning
confidence: 99%